Poetic Presence and Illusion Essays in Critical History and Theory - Krieger, Murray (Johns Hopkins University Press, 2019)
Orignally published in 1979. Poetic Presence and Illusion brings together Krieger's speculation on literature and its effect on the reader. The poem, Krieger argues, is an illusionary presence and an ever-present illusion. It exists for the reader, like a drama before an audience, only within an illusionary context. But the illusion should not be taken lightly as a false substitute for reality. It is itself a real and positive force: it is what we see and, as such, is constitutive of our reality, even if our critical faculty de-constitutes that reality by viewing it as no more than an illusion. The coupling of poetic presence and poetic illusion serves to describe the relationship between poetry as metaphor and the reader's sense of personal and poetic reality. Krieger examines the workings of selected Renaissance and contemporary poems with regard to this dual nature and evaluates the work of literary critics (himself included) who have been concerned with this doubleness. Poetic Presence and Illusion allows readers who have read Krieger's earlier work to understand the development of his critical position.